Determination of Parameters for Limiting Longitudinal Acceleration to Optimize Energy Consumption for Train Traction - Bobyr, D. V.; Bodnar, E. B.; Kisliy, D. M.; Desiak, A. Y. (Science and Transport Progress, 2023)
Purpose. The main purpose of the article is to improve traction calculations using mathematical modeling when solving the equation of train motion. The train model is adapted to optimize the parameters of train movement during speed gain with the determination of functional relationships between the power of the locomotive power plant and the profile of the track section with the consumption of energy resources by the locomotive. Methodology. Modern methods of mathematical modeling were used to solve the tasks. The modeling of the power plant operation was performed using interpolation and approximation methods. The simulation modeling method was used to create a model of the electrical part of the diesel locomotive transmission. The method of integrating the differential equation of motion was used to calculate the parameters and nature of the train's movement and the problem was solved, which consists in finding a solution to this equation over the length of the traction section, taking into account the variable values of the locomotive power and the slopes of the track profile. Findings. To analyze the results of traction calculations, we obtained such indicators as technical speed and diesel fuel consumption, and compared these indicators. The results show that in the case of acceleration limitation, there is a decrease in diesel fuel consumption at almost unchanged technical speed. Originality. The improvement of energy efficiency of train operation has been further developed, namely, the functional dependence of the relative power of the locomotive power plant, which takes into account the actual profile of the site, has been obtained, which makes it possible to determine energy-saving modes of locomotive control and reduce energy consumption, load on the diesel engine and elements of the diesel locomotive traction transmission during transient modes, which, in turn, in addition to saving diesel fuel, will affect the reliability of the power plant elements. The practical value of the study is to save diesel fuel in the modes of movement that provide speed gain and increase the reliability of the power plant due to reduced load.